2007
DOI: 10.1051/0004-6361:20066627
|View full text |Cite
|
Sign up to set email alerts
|

The light variability of the helium strong star HD 37776 as a result of its inhomogeneous elemental surface distribution

Abstract: We simulate light curves of the helium strong chemically peculiar star HD 37776 assuming that the observed periodic light variations originate as a result of inhomogeneous horizontal distribution of chemical elements on the surface of a rotating star. We show that chemical peculiarity influences the monochromatic radiative flux, mainly due to bound-free processes. Using the model of the distribution of silicon and helium on HD 37776 surface, derived from spectroscopy, we calculate a photometric map of the surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 42 publications
(71 reference statements)
2
100
0
Order By: Relevance
“…Molnar concluded that neither the photometric variability nor the ultraviolet Si line variations were due to a variation in T eff over the rotation cycle of the star. Krticka et al (2007) have also demonstrated that the light curve of the heliumstrong star HD 37776, an object quite comparable to a Cen in fundamental properties and in having quite pronounced line profile variations, can be almost completely accounted for by the inhomogeneous surface distribution of silicon and helium over the star's surface and the bound-free transitions of these elements and not surface temperature variations. More recent work on a cooler Ap star, HR 7224, also suggests that surface temperature variations do not exist in Ap stars (Krticka et al 2009).…”
Section: Doppler Imagingmentioning
confidence: 90%
“…Molnar concluded that neither the photometric variability nor the ultraviolet Si line variations were due to a variation in T eff over the rotation cycle of the star. Krticka et al (2007) have also demonstrated that the light curve of the heliumstrong star HD 37776, an object quite comparable to a Cen in fundamental properties and in having quite pronounced line profile variations, can be almost completely accounted for by the inhomogeneous surface distribution of silicon and helium over the star's surface and the bound-free transitions of these elements and not surface temperature variations. More recent work on a cooler Ap star, HR 7224, also suggests that surface temperature variations do not exist in Ap stars (Krticka et al 2009).…”
Section: Doppler Imagingmentioning
confidence: 90%
“…The photospheric line profiles of these elements hence vary with the rotation period of the star, and the variations in the lines from different elements are typically not identical (e.g., Briquet et al 2001Briquet et al , 2004Lehmann et al 2006). In addition, stars with a patchy surface abundance pattern are known to show rotationally modulated light variability (Krtička et al 2007(Krtička et al , 2009. From the Hipparcos light-curve of HD 202850, Koen & Eyer (2002) derived a putative (but not yet confirmed) period of 120.2 d. This period might be caused by stellar rotation, but the value of sin i = 33 ± 2 km s −1 obtained by Markova & Puls (2008) limits the rotation period to P ≤ (83 ± 5) d.…”
Section: Discussionmentioning
confidence: 97%
“…It is also one of the few spotted stars for which the rotational spin-down has been directly measured (Mikulášek et al 2008) and the light variations were explained with a physically realistic star-spot model (Krtička et al 2007). Uniquely for an early-type chemically peculiar star, HD 37776 shows a complex double-wave longitudinal magnetic field variation (Thompson & Landstreet 1985), suggesting that its magnetic field topology significantly departs from an oblique dipolar field common for other Bp stars.…”
Section: Hd 37776mentioning
confidence: 96%